Error compensation during finger force production after oneand four-finger voluntarily fatiguing exercise - Kruger, Eric S. (2007)
The effect of muscle fatigue on error compensation strategies during multi-finger ramp force production tasks was investigated. Thirteen young, healthy subjects were instructed to produce a total force with four fingers of the right hand to accurately match a visually displayed template. The template consisted of a 3-s waiting period, a 3-s ramp force production (from 0 to 30% maximal voluntary contraction, MVC), and a 3-s constant force production. A series of twelve ramp trials was performed before and after fatigue. Fatigue was induced by a 60-s maximal isometric force production with either the index finger only or with all four fingers during two separate testing sessions. The average percent of drop was 38.2% in the MVC of the index finger after index-finger fatiguing exercise and 38.3% in the MVC of all fingers after four-finger fatiguing exercise. The ability of individual fingers to compensate for each other's errors in order for the total force to match the preset template was quantified as the error compensation index (ECI), i.e. the ratio of the sum of variances of individual finger forces and the variance of the total force. By comparing pre- and post-fatigue performance during four-finger ramp force production, we observed that the variance of the total force was not significantly changed after one- or four-finger fatiguing exercise. The ECI significantly decreased after four-finger fatiguing exercise, especially during the last second of the ramp; while the ECI remained unchanged after index finger single-finger fatiguing exercise. These results suggest that the central nervous system is able to utilize the abundant degrees of freedom to compensate for partial impairment of the motor apparatus induced by muscle fatigue to maintain the desired performance. However, this ability is significantly decreased when all elements of the motor apparatus are impaired.